Malaysia halal food product packaging strategy in the Middle East and North Africa (MENA) region - Abdul Jabar, Mohd Azidan; Hasan Adali, Nor Asyikin; Ismail, Muhd Zulkifli; Wan Sulong, Wan Muhammad; Hassan, Abd Rauf (Human Resource Management Academic Research Society, 2024)
Packaging is a major marketing element as it can influence the purchasing decision of the consumer at the point of sale, especially for food products. Therefore, this research aims to explore as well as to discuss the packaging strategy implemented by the halal food industry in Malaysia in marketing food products in the MENA region. This research is a qualitative research which was done by conducting semi structured interviews of 20 halal food product industries in Malaysia that export food products to the MENA region. The technique used to analyse the findings of the qualitative interviews is the thematic content analysis approach. The findings of the research were that the industry gives attention to the language and cultural aspects for the packaging of food products marketed in the MENA region. Several Arabic language usage strategies specifically for labelling, branding and product slogan were applied by the industry. The findings of this research are significant for new industries which have plans to market products to the MENA region.